2017
DOI: 10.1038/s41598-017-09460-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and structural determination of a new anti-MET function-blocking antibody with binding epitope distinct from the ligand binding domain

Abstract: The growth and motility factor Hepatocyte Growth Factor/Scatter Factor (HGF/SF) and its receptor, the product of the MET proto-oncogene, promote invasion and metastasis of tumor cells and have been considered potential targets for cancer therapy. We generated a new Met-blocking antibody which binds outside the ligand-binding site, and determined the crystal structure of the Fab in complex with its target, which identifies the binding site as the Met Ig1 domain. The antibody, 107_A07, inhibited HGF/SF-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(92 reference statements)
1
5
0
Order By: Relevance
“…In fact, in many affinity maturation campaigns much of the original amino acid sequence is restored in the high affinity "solutions". 21,23 Thus, the smaller library size required by the directed mutagenic approach used here scales well with the potential size of mammalian display libraries. Such a targeted approach is possible by novel synthesis technology enabling the economic synthesis of 10,000s oligonucleotides.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In fact, in many affinity maturation campaigns much of the original amino acid sequence is restored in the high affinity "solutions". 21,23 Thus, the smaller library size required by the directed mutagenic approach used here scales well with the potential size of mammalian display libraries. Such a targeted approach is possible by novel synthesis technology enabling the economic synthesis of 10,000s oligonucleotides.…”
Section: Discussionmentioning
confidence: 84%
“…In many cases, it is found that improved clones are related in sequence to the parental sequence. 23 A more efficient and parsimonious route for mutagenesis therefore is to retain sequence information while exploring the surrounding sequence space. To achieve this, oligonucleotides were designed to a continuous stretch of eight amino acids in the CDR3 of VH and VLs such that every possible 2-mer and 1-mer variant, using all amino acids (with the exception of cysteine) were included (Figure 4(a,b)).…”
Section: Creation and Selection Of A Stable Population Of Antibody-pmentioning
confidence: 99%
“…To our knowledge it is the first time that such alteration of HGF/SF-MET interaction is evidenced according to the cellular context and thus could represent a novel molecular mechanism to regulate the MET receptor downstream signaling. Interestingly, recent structural data suggest the existence of two distinct states of MET receptor (open/close conformation) allowing or not ligand binding [ 66 ]. It is worth noticing that potential action of phosphatases and decrease of the HGF/SF-MET interaction could synergically contribute to decrease MET phosphorylation observed during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of pathway cascades allows particular definitions of oncogenesis to emerge as dynamics of an initial cell response; autonomous inhibitory biology systems may be viewed as being well-delineated morphologically, and also genetically, in terms of mutability and impaired DNA repair systems. The "compact" conformation of the MET extracellular domain is important and relevant to HGF/Scatter factor binding and signaling [23].…”
Section: Substantiation Of the Integral Transformation Eventmentioning
confidence: 99%